1. ## laplace help please very urgent

Please can someone help me out of my misery.

My question is how can I solve this equation:

2CE e-3at u(t)-u(t-2t)

I have replaced t with t= [(t-2T)+2T]

now I have q(t) = 2CE e-3a[(t-2T)+2T] u[(t-2T)+2T]-u(t-2T)

so I have crossed out the delay of 2T = e-2Ts

so I am left with q(t) = 2CE e-3a(t+2T) u(t+2T)-u(t)

I am now lost and have no idea what to do next.

Please can someone put me out of my misery.

2. Originally Posted by darren1971
Please can someone help me out of my misery.

My question is how can I solve this equation:

2CE e-3at u(t)-u(t-2t)

I have replaced t with t= [(t-2T)+2T]

now I have q(t) = 2CE e-3a[(t-2T)+2T] u[(t-2T)+2T]-u(t-2T)

so I have crossed out the delay of 2T = e-2Ts

so I am left with q(t) = 2CE e-3a(t+2T) u(t+2T)-u(t)

I am now lost and have no idea what to do next.

Please can someone put me out of my misery.
No-one has probably replied so far because, like me, they can't make sense of what you've posted. Problems with what you've posted include (but are not limited to):

1. There's no equation given to solve. Equations have an equal sign (=) in them.

2. What is CE meant to represent?

3. Is e-3at meant to be $\displaystyle e^{-3at}$. If so, it should at least be written as e^(-3at).

4. "I have replaced t with t= [(t-2T)+2T]" makes no sense.

If you want help, especially urgent help, you will need to be much much clearer.